Cover Picture: Four‐Step Domino Reaction Enables Fully Controlled Non‐Statistical Synthesis of Hexaarylbenzene with Six Different Aryl Groups (Angew. Chem. Int. Ed. 41/2021). Issue 41 (3rd September 2021) - Grau, Benedikt W.; Dill, Maximilian; Hampel, Frank; Kahnt, Axel; Jux, Norbert; Tsogoeva, Svetlana B.
Abstract : Hexaarylbenzene scaffolds, containing six different aromatic rings around the central benzene core, are a synthetic challenge. In their Research Article on page 22307, Svetlana B. Tsogoeva et al. report a process that allows the simple and straightforward generation of such hexaarylbenzenes (HABs). In an efficient, two‐component four‐step domino reaction, a functionalized triarylbenzene is formed and used as a key intermediate to furnish asymmetrically substituted HABs in high overall yield and without involvement of statistical steps.